2017
DOI: 10.1007/s00464-017-5481-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of self-expandable metallic stent placement intraluminal 125I seed strands brachytherapy of malignant biliary obstruction

Abstract: Participants were randomly assigned to receive treatment with a self-expandable metallic stent (SEMS) placement combined with intraluminal I seed strands brachytherapy (brachytherapy group) or a SEMS without brachytherapy (control group). The outcomes were measured in terms of technical success, clinical success, stent patency, complications related to the procedure, and patient survival. A P value of less than 0.05 indicated a significant difference. Results There were no significant differences in technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 32 publications
4
59
1
Order By: Relevance
“…The pooled HR value indicated that ISS can significantly improve patients’ survival. This result is consistent with findings from other meta-analyses regarding ISS insertion for malignant biliary obstruction patients [ 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The pooled HR value indicated that ISS can significantly improve patients’ survival. This result is consistent with findings from other meta-analyses regarding ISS insertion for malignant biliary obstruction patients [ 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“… 6 Although it is a safe treatment, the cumulative brachytherapy dose is relatively low and fibrous connective tissue in the bile duct could reduce the local irradiation effect. 7 To eliminate these disadvantages, a novel brachytherapy biliary drainage catheter (BBDC) loaded with double 125 I seed strands was designed. Of note, the efficacy and complication of the treatment for MOJ have not been largely studied to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, CSEMSs had a higher stent migration rate than UCSEMSs [ 21 ]. Studies [ 18 , 22 , 23 ] have also shown that compared with stent placement alone, placement of an irradiation stent could provide survival benefit and prolong stent patency in malignant obstructive jaundice. However, unlike biliary malignant tumors, obstructive jaundice caused by pancreatic carcinoma is often eccentric stenosis due to tumor oppression.…”
Section: Discussionmentioning
confidence: 99%